2006
DOI: 10.1158/0008-5472.can-06-3171
|View full text |Cite
|
Sign up to set email alerts
|

Human Arrest Defective 1 Acetylates and Activates β-Catenin, Promoting Lung Cancer Cell Proliferation

Abstract: Arrest defective 1 (ARD1), an acetyltransferase, is essential for the yeast life cycle. Although its human homologue (hARD1) has been identified, its biological functions in human cells remain unclear. In the present study, we examined the biological function of hARD1. In H1299 and A549 lung cancer cells, hARD1-silencing RNA inhibited cell proliferation and induced G 1 arrest. Cyclin D1 was also found to be downregulated in these growth-arrested cells, and the ectopic expression of cyclin D1 rescued cell growt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
159
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 135 publications
(172 citation statements)
references
References 20 publications
13
159
0
Order By: Relevance
“…A growing body of evidence has suggested that NAA10 has diverse functions beyond the cotranslational modification. NAA10 can catalyse amino-terminal a-acetylation or lysine e-acetylation in many proteins as post-translational modification [17][18][19]30 , and our results provide additional support for this role of NAA10. Moreover, given our result showing that recombinant NAA10 catalyses lysyl acetylation without auxiliary partners, NAA10 is likely to have its enzymatic activity as a monomer.…”
Section: Naa10 Negatively Regulates Bone Development In Micesupporting
confidence: 65%
See 4 more Smart Citations
“…A growing body of evidence has suggested that NAA10 has diverse functions beyond the cotranslational modification. NAA10 can catalyse amino-terminal a-acetylation or lysine e-acetylation in many proteins as post-translational modification [17][18][19]30 , and our results provide additional support for this role of NAA10. Moreover, given our result showing that recombinant NAA10 catalyses lysyl acetylation without auxiliary partners, NAA10 is likely to have its enzymatic activity as a monomer.…”
Section: Naa10 Negatively Regulates Bone Development In Micesupporting
confidence: 65%
“…A polyclonal antibody against NAA10 was raised in rats against full-length human NAA10 (ref. 17). Mouse NAA10 and b-tubulin primary antibodies and horseradish peroxidase-conjugated secondary antibodies were purchased from Santa Cruz Biotechnology (Santa Cruz, CA); anti-Runx2 from MBL (Nagoya, Japan); Acetylated-Lysine antibody from Cell Signaling Technologies (Billerical, MA); anti-a-Myc-tag and Flag-tag antibody from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations